KELUARGA SEJAHTERA DALAM SISTEM NILAI BUDAYA LINTANG (Studi Kasus Pada Desa Tanjung Tawang Kecamatan Muara Pinang Dan Desa Rantau Alih Kecamatan Lintang Kanan) - Antonio Imanda (UNIVED PRESS, Universitas Dehasen Bengkulu, 2015)
This study was conducted to describe the prosperous families in Lintang society as well as to describe Lintang society perceptions towards a prosperous family in their cultural values system. This study explored and analyzed the views and perceptions of Lintang society toward prosperous family and cultural values system that influence the behavior of a prosperous. This research was a qualitative descriptive study. Research targets were families in Lintang society. Data were collected by interviews, observations and documentation techniques. The result of this study showed that the families prosperity in Lintang society was always changing. Besides influenced by the crop and coffee prices, the prosperity wass also influenced by cultural values that influence people's behavior in building a prosperous family. Some of the most striking things were: Musim Kawo (coffee season), the harvest of coffee that increased the prosperity and consumption levels of society, Musim Sedekah (summer party) after the harvest season, a season in which people competing to organize a massive party, Musim Bejudi (gambling season), at the time the party was also followed by a period of gambling, and Musim Paceklik (dry season) because the crop was up, people didn’t have any savings so that people experiencing difficulty in meeting the needs of everyday life, this kind of thing goes annually.Keywords: Prosperous Family, Lintang, Cultural Values System